Analyzing the improvement of the receiver signal level and receiver signal quality in Terengganu: article - Hashim, Roszana (2011)
The aims of this project are to study receiver signal level and receiver signal quality in the different situation such as the comparison result about receiver signal level and receiver signal quality before and after the repeater were placed at the sample area. The project started with the application of using the coverage area data from OPTLX GLOBAL SDN BHD. The data was converted from TEMS software to database using Oracle Database lOg Express Edition software. The Oracle database lOg Express Edition was chosen because this is a one of the multifunction database such as the Oracle Database lOg Express Edition software which can manage the collected data and store the data at the same time. Finally, the data at the database will be simulated using the MATLAB software to plot the graph pattern of the receiver signal level and receiver quality level before and after the repeater is placed at the sample area. In addition, the programming command was designed based on the range of the signal value to display the condition of the receiver signal level and receiver signal quality at the sample area.